The role of Best Available Techniques (BAT) and limit values in defining the scope of lawful risks in environmental criminal law - Stefano Zirulia (Lexambiente, 2019)
This paper addresses the issue of criminal responsibility of the operators of industrial facilities subject to authorisation (according to IED directive) for offenses to the environment and human health caused by polluting activities formally compliant with the Best Available Techniques and related limit values as defined at European level. The objective is to establish the extent to which these parameters contribute to the definition of areas of “permitted risk” suitable to shield operators from charges for environmental crimes.